ARTI RUMAH TINGGAL BAGI ORANG SUNDA - Tetty Sekaryati (Jurnal Dimensi Seni Rupa dan Desain, 2007)
AbstractMostly house structures for living are based on the concept from the roots of nature (cosmos) which is depicted through myths, religions or beliefs. Reflection of strenght outside the human being are frequcntly realized in so ninny aspects, for example in the shape of buildings, space arrangements and also the implementation of the element of decoration.This article is aniffbrt to express the meaning of house structures for the Sundanese like the one told by Romo Mangunwijaya , a cultural observer, the houses we are building are house for human beings. Therefore it is actually something that always reflects the breath of human life by tendencies and character, by the aspirations and passions. In general traditional architectural device which is based on the concept of the Sundanese people has integrated with nature. Nature is strength or potency which must be wisely accurately in everyday life.keyword: Stmdanese housesAbstrakSebagian besar konsep dasar bangunan rumah tinggal bersumber dari alam (kosmos) yang digambarkan melalui mitos-mitos, kepercayaan atau agama. Refleksi kekuatan di luar manusia tersebut acapkali diwujudkan d a la m berbagai hal, misalnya dalam wujud bangunan, penataan ruang maupun penggunaan elemen dekorasi.Tulisan ini acialah upaya mengungkap arti bangunan rumah tinggal bagi orang Sunda seperti yang dikatakan oleh Romo Mangunwijaya seorang Budayawan, bahwa rurnah yang kita bang-un ialah rumah manusia. Oleh karena itu merupakan sesuatu yang sebenarnya selalu dinapasi oleh kehidupan manusia, oleh watak dan kecenderungan-kecenderungan, oleh nafsu dan cita‑citanya. Secara Umum konsep  dasar rancangan arsitektur tradisional masyarakat Sunda adalah menyatu dengan alam. Alam meripakan sebuah potensi atau kekuatan yang mesti dihormati serta dimanfaatkan secara tepat di dalam kehidupan sehari-hari